In-silico structural analysis of E509K mutation in LARGE and T192M mutation in Alpha Dystroglycan in the inhibition of glycosylation of Alpha Dystroglycan by LARGE. (October 2016) - Bhattacharya, Simanti; Das, Amit; Bagchi, Angshuman
Graphical abstract: Highlights: E509K mutation of LARGE causes MDDGB6. Structure of LARGE is altered due to this E509K mutation. Glucuronic acid binding ability of LARGE is weakened due to E509K mutation. E509K mutation hampers the interaction between LARGE and Alpha Dystroglycan. Abstract: Impaired glycosylation of cellular receptor Alpha Dystroglycan (α-DG) leads to dystroglycanopathy. Glycoprotein α-DG is the receptor protein in the Dystrophin Associated Protein Complex (DAPC), a macromolecular gathering on muscle cell membrane to form a bridge between extracellular matrix (ECM) and cellular actin cytoskeleton. Proper glycosylation of α-DG is mediated by the glycosylating enzyme LARGE. Mutations either in α-DG or in LARGE lead to improper glycosylations of α-DG thereby hampering the formation of final Laminin binding form α-DG resulting in dystroglycanopathy. In our current work, we explored the structural changes associated with the presence of mutations in α-DG as well as in the enzyme LARGE. We further extended our research to understand the effect of the mutations onto protein-enzyme interactions. Moreover, since LARGE transfers the sugar moiety (glucuronic acid; GlcA) onto α-DG, we tried to analyze what effect the mutation in LARGE confers on this enzyme ligand interaction. This work for the first time addressed the molecular changes occurring in the structures α-DG, LARGE and their interactions and shed lights on the as yet poorly understood mechanism behind the dystroglycanopathy onset.